2019
DOI: 10.2196/16273
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Wristband Fitbit Models in Assessing Sleep: Systematic Review and Meta-Analysis

Abstract: BackgroundWearable sleep monitors are of high interest to consumers and researchers because of their ability to provide estimation of sleep patterns in free-living conditions in a cost-efficient way.ObjectiveWe conducted a systematic review of publications reporting on the performance of wristband Fitbit models in assessing sleep parameters and stages.MethodsIn adherence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, we comprehensively searched the Cumulative In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
187
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(199 citation statements)
references
References 45 publications
(102 reference statements)
5
187
2
5
Order By: Relevance
“…On the other hand, our findings might also be explained by an overestimation of wakefulness during sleep (WASO) by newer actigraph devices, especially in young children (Meltzer et al 2012). Proper sleep assessment is a function of both the hardware and interpretative algorithm technologies (Haghayegh et al 2019(Haghayegh et al , 2020. A previous study in 13 older children (10-14 years) that used the same actigraph (ActiGraph wGT3X-BT, Pensacola, FL, USA) and algorithm (Sadeh) as we did also show an underestimation of TST by an average of 49 min, an overestimation of WASO by an average of 59 min, and hence an 11.6% lower SE, compared to the golden standard (PSG) (Quante et al 2018).…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, our findings might also be explained by an overestimation of wakefulness during sleep (WASO) by newer actigraph devices, especially in young children (Meltzer et al 2012). Proper sleep assessment is a function of both the hardware and interpretative algorithm technologies (Haghayegh et al 2019(Haghayegh et al , 2020. A previous study in 13 older children (10-14 years) that used the same actigraph (ActiGraph wGT3X-BT, Pensacola, FL, USA) and algorithm (Sadeh) as we did also show an underestimation of TST by an average of 49 min, an overestimation of WASO by an average of 59 min, and hence an 11.6% lower SE, compared to the golden standard (PSG) (Quante et al 2018).…”
Section: Discussionmentioning
confidence: 83%
“…With respect to sleep, our results in general medicine patients (R = 0.19, P = 0.24) did not show correlation with self-reported sleep. While a systematic review of Fitbit-based sleep assessment found that later versions of devices similar to the model that we used correlated well with total sleep time and sleep e ciency as measured by gold standard polysomnography, 24 all studies were either in the participant home or a sleep lab, and none were in hospitalized patients. Indeed, our results were similar to results found in ICU patients (R = 0.33, P = 0.03) with self-reported sleep.…”
Section: Discussionmentioning
confidence: 91%
“…Ultimately, device algorithms will likely improve further; improvements in sleep stage detection have already been demonstrated in newer devices compared to the previous generation. 24 As existing algorithms for determining sleep and steps were not developed using data from hospitalized patients, it is not surprising that these devices are less accurate in the hospital setting. Further re nement of these devices in collaboration with device manufacturers is necessary.…”
mentioning
confidence: 99%
“…Of note, a systematic review of eight studies looking at Fitbit-based sleep assessment found that later versions of devices similar to the model that we used correlated well with total sleep time and sleep e ciency as measured by gold standard polysomnography. 28 These Fitbit models showed a sensitivity of 0.95-0.96 and a speci city of 0.58-0.69 in detecting sleep periods. However, all studies were either in the participant home or a sleep lab, and none were in hospitalized patients.…”
Section: Discussionmentioning
confidence: 92%